CAN RELIANCE ON MULTIPLE PERFORMANCES MEASURES (RMPM) BOOST EMPLOYEE PRODUCTIVITY THROUGH EMPLOYEE LOYALTY? - Putri, Marthalia; Yuliansyah, Yuliansyah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The aim of the study is to investigate the extent to which reliance on multiple performances measures (RMPM) leverages employee productivity. Assuming that this relationship exists when an employee has a high level of loyalty, we survey nurses and doctors in several healthcare organisations in Bandar Lampung. Ã‚Â Eighty-two returned surveys yielded usable datasets from 76 respondents. Analysing data with SPSS 19.0, we found that RMPM can leverage employee productivity through employee loyalty, but we found no direct effect of RMPM on employee productivity. Ã‚Â This study enriches research on management accounting and on employee behaviour in the service sector, in particular in health care organizations.